Measurement of Protein Content in Extract of Earthworm - Ahmad Fauzi; Wahyu Utami; Denny Vitasari; Arifah Sri Wahyuni (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Earthworms are widely used by Indonesian people as an alternative treatment of typhoid fever in addition to the main treatment using antibiotics. One of the main ingredients of earthworms (Lumbricus rubellus) is protein. The amount of protein content of the extracts is highly dependent on the production process. For this reason, a spectrophotometric analysis was carried out to determine the protein content of the worm extracts in the market. As a result of the analysis using the Lowry method at a maximum wavelength of 650.8 nm, the protein content of a sample of earthworm extract obtained from the market was (10.41 ± 0.47) %.